2023
DOI: 10.1039/d2cp04204e
|View full text |Cite
|
Sign up to set email alerts
|

Excited-state and charge-carrier dynamics in binary conjugated polymer dots towards efficient photocatalytic hydrogen evolution

Abstract: Aqueous dispersed conjugated polymer dots (Pdots) have shown promising application in photocatalytic hydrogen evolution. To efficiently extract photogenerated charges from the type-II heterojunction Pdots for hydrogen evolution, the mechanistic study...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…To mitigate electron-hole recombination for PSs, previous reports have focused more on designing PS skeletons to facilitate the intersystem crossing process or using locally distributed and exhaustible substances, such as GSH and NADH, to scavenge holes. In addition, the PDT-related photosensitized reaction of the currently reported PSs mainly occur on the surface of the PS nanoparticles with substances, such as GSH and NADH, due to the strong hydrophobicity of PSconjugated skeletons and alkyl side chains, and the large size of substances 45,58,63 . By contrast, we provided a simple strategy of attaching glycol oligomers instead of alkyl groups as side chains to organic PS skeletons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To mitigate electron-hole recombination for PSs, previous reports have focused more on designing PS skeletons to facilitate the intersystem crossing process or using locally distributed and exhaustible substances, such as GSH and NADH, to scavenge holes. In addition, the PDT-related photosensitized reaction of the currently reported PSs mainly occur on the surface of the PS nanoparticles with substances, such as GSH and NADH, due to the strong hydrophobicity of PSconjugated skeletons and alkyl side chains, and the large size of substances 45,58,63 . By contrast, we provided a simple strategy of attaching glycol oligomers instead of alkyl groups as side chains to organic PS skeletons.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, most electron-hole pairs need to successfully migrate to the PS nanoparticle's surface in order to participate in the photosensitive reaction with substances for these PSs. Unfortunately, the migration length of electron-hole pairs is typically less than 20 nm 45 . Thus, these PSs generally required a relatively high-power photoexcitation (>100 mW cm −2 ) 39,46 , leading to undesirable side effects.…”
mentioning
confidence: 99%
“…Several other studies on nanoprecipitated polymer nanoparticles have investigated heterojunction systems; 57 59 a study on a nanoparticle blend of F8TBT donor polymer and ITIC acceptor showed, similar to the nanoemulsion systems, that highly intermixed nanoparticle morphologies give efficient charge carrier generation but that this structure also leads to increased charge recombination and limits the further utilization of free charges. 57 This is analogous to many OPV blends where the degree of donor–acceptor intermixing must be finely balanced, enough blending to give efficient charge separation but not so much that charge recombination becomes dominant.…”
Section: Opv Materials For Photocatalytic Hydrogen Productionmentioning
confidence: 99%
“…Heterostructures are also employed in energy conversion technologies, such as in solar cells, where they convert light into electrical energy [ 191 ]. The “D-A Strategy” is commonly used in preparing NIR optical nanoprobes [ 49 , 192 ]. Pdots with simpler structures serve as energy donors (D), and the introduction of molecular groups with higher emission peaks as acceptors (A) facilitates NIR emission through ET strategies, as shown in Fig.…”
Section: Characterization and Spectral Properties Of Semiconducting P...mentioning
confidence: 99%